Correlation of single‐breath count test and neck flexor muscle strength with spirometry in myasthenia gravis. Issue 1 (January 2016) - Elsheikh, Bakri; Arnold, W. David; Gharibshahi, Shahram; Reynolds, Jerold; Freimer, Miriam; Kissel, John T.
ABSTRACT: Introduction : Although formal spirometry is the gold standard for monitoring respiratory function in patients with myasthenia gravis (MG), such testing is often delayed or unavailable. There is a need for a simple bedside test that can accurately measure respiratory function. Methods : We conducted a prospective, cross‐sectional, single‐blind study in adults with acetylcholine receptor antibody positive MG. Participants performed the single breath count test (SBCT) and underwent manual muscle strength testing, and a respiratory therapist performed spirometry blinded to SBCT and strength results. Results : Thirty‐one patients, aged 57 ± 19 years participated. SBCT showed significant correlations with forced vital capacity (FVC), negative inspiratory force, and neck flexor strength ( P < 0.01). FVC showed significant correlation with neck flexor strength ( P = 0.02) but no correlation with shoulder abductor strength. Conclusions : These data suggest that the SBCT and neck flexor strength testing are valuable tools for bedside assessment of respiratory function in MG patients. Muscle Nerve 53 : 134–136, 2016